PENERAPAN MODEL PEMBELAJARAN CERMAT UNTUK MENINGKATKAN AKTIVITAS, KETERAMPILAN KOMUNIKASI DAN KERJASAMA PADA MUATAN IPAS KELAS V SDN TELUK DALAM 1 BANJARMASIN - Dania; Noorhapizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low level of student activity, communication skills, collaboration, and learning outcomes due to limited engagement and poor ability to express ideas. To address this, the CERMAT learning model was implemented. The study aimed to examine improvements in teacher and student activity, communication skills, collaboration, and learning outcomes. A qualitative approach was used with Classroom Action Research (CAR) conducted over four meetings involving 21 fifth-grade students at SDN Teluk Dalam 1 Banjarmasin in the 2024/2025 academic year. Data were collected through observation and written tests. The results showed significant improvement in all aspects: teacher activity increased from a score of 26 to 34, student activity from 34% to 97%, communication from 52% to 95%, collaboration from 57% to 100%, and student learning outcomes improved classically.